Building Blocks for Good Governance in Cameroon Schools: Survey of Government Secondary Schools of Garoua 1 Sub-Division, North Region of Cameroon - Takang Jaspa David (International Journal on Integrated Education, 2022)
South East European University in Macedonia in 2010 introduced five key words (building blocks) for good governance which can be applied in any organization (participation, strategic vision, performance, accountability, transparency). These key words were validated by the United Nations Development Program and veted to be good governance assessment methodology. This methodology provided the tools for assessing the governance in the education sector. This study titled “BUILDING BLOCKS FOR GOOD GOVERNANCE IN CAMEROON SCHOOLS: SURVEY OF GOVERNMENT SECONDARY SCHOOLS OF GAROUA 1 SUB-DIVISION, NORTH REGION OF CAMEROON” endeavor to find out whether these key words listed above are applied in Cameroonian secondary schools for good governance. To come out with the findings, 4 government secondary schools were selected randomly out of 6 in the Garoua 1 sub-division. In each school, one vice-principal and one discipline master, fifteen teachers, and 5 students where conveniently selected making a total of seventy three (73) participants of the study. Following the survey, statistical package for social sciences (SPSS) was used to analyze the data using frequencies, tables and percentages. To corroborate the findings, an interview schedule was generated and was administered to the Divisional Delegate of Secondary Education for the Benoue Division and the Regional Delegate of Secondary Education for the North Region of Cameroon. The main finding of the study shows that most schools surveyed use mainly participation and performance which in the most part were epileptically used. The researcher concluded by recommending a more versatile approach in school governance using all the key words (building blocks) and recommended regular seminars and workshops, production of leaflets regarding the key words for school administrators and teachers on how they can be effectively applied in governing schools.